2021
DOI: 10.1038/s41598-021-82183-7
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics and evolutionary history of the endangered Eld’s deer (Rucervus eldii) with implications for planning species recovery

Abstract: Eld's deer (Rucervus eldii) with three recognised subspecies (R. e. eldii, R. e. thamin, and R. e. siamensis) represents one of the most threatened cervids found in Southeast Asia. The species has experienced considerable range contractions and local extinctions owing to habitat loss and fragmentation, hunting, and illegal trade across its distribution range over the last century. Understanding the patterns of genetic variation is crucial for planning effective conservation strategies. This study investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 88 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…The taxonomic classification of Eld's deer has been a subject of discussion (Pitra et al, 2004;Heckeberg, 2020;Ghazi et al, 2021;Wong et al, 2021). Some sources assign Eld's deer to the distinct genus Panolia following the nomenclature used by John Edward Gray in 1843 (Gray, 1843).…”
Section: Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…The taxonomic classification of Eld's deer has been a subject of discussion (Pitra et al, 2004;Heckeberg, 2020;Ghazi et al, 2021;Wong et al, 2021). Some sources assign Eld's deer to the distinct genus Panolia following the nomenclature used by John Edward Gray in 1843 (Gray, 1843).…”
Section: Nomenclaturementioning
confidence: 99%
“…This designation is followed by the Species Survival Commission of the IUCN, as well as the AZA; thus, we use it here. However, some recent molecular studies have included Eld's deer in the genus Cervus (Balakrishnan et al, 2003;Angom et al, 2017;Ghazi et al, 2021). The deer examined by the current study were exclusively from the subspecies R. e. thamin.…”
Section: Nomenclaturementioning
confidence: 99%
“…Eld's deer belongs to the order Artiodactyla, family Cervidae, subfamily Cervinae and tribe cervini. Eld's deer share morphological resemblances with swamp deer (R. duvaucelii) and the extinct Schomburgk's deer (R. schomburgki) (Ghazi et al 2021). The species is classified in the genus Rucervus, which is currently adopted by the International Union for Conservation of Nature (Gray et al 2015).…”
Section: Taxonomymentioning
confidence: 99%
“…The species is classified in the genus Rucervus, which is currently adopted by the International Union for Conservation of Nature (Gray et al 2015). However, Ghazi (2021) has suggested that the three species classified under the genus Rucervus (R. duvaucelii, R. schomburgki and R. eldii) are extremely different and the classification of Eld's deer in Rucervus is phylogenetically inappropriate. Contrary to different perspectives based on morphological and karyotypic classification, molecular studies based on mitochondrial and nuclear markers suggest that the placement of Eld's deer along with several other species, including Elaphurus davidianus, Przewalski albirostris and all species of the genus Rusa, to the genus Cervus is phylogenetically more appropriate (Hu et al 2019).…”
Section: Taxonomymentioning
confidence: 99%
See 1 more Smart Citation